Managing price and financial stability objectives in inflation targeting economies in Asia and the Pacific - Kim, Soyoung; Mehrotra, Aaron (Journal of Financial Stability, 2017)
Many central banks have adopted explicit objectives for financial stability, raising the possibility of trade-offs between price and financial stability objectives. Based on structural vector autoregressions that incorporate both monetary and macroprudential policy shocks for four inflation targeting economies in Asia and the Pacific, we analyse the role of each policy shock in explaining deviations from the other policy’s objective, by applying historical decompositions. The macroprudential measures used in the study affect credit extended to the private sector. We find that there are periods when macroprudential policy shocks have contributed to pushing inflation away from the central bank’s inflation target and when monetary policy shocks have contributed to buoyant credit, suggesting that there have been short-term trade-offs between price and financial stability objectives. However, we also find periods when macroprudential policy shocks helped stabilise inflation and monetary policy shocks contributed to financial stability.